2014
DOI: 10.1111/cas.12388
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution genomic copy number profiling of primary intraocular lymphoma by single nucleotide polymorphism microarrays

Abstract: Primary intraocular lymphoma (PIOL) is a rare lymphoma. Because of difficulties in obtaining tissue samples, little is known about the disease's genetic features. In order to clarify these features, we carried out single nucleotide polymorphism array karyotyping of IOL using genomic DNA extracted from vitreous fluid. We analyzed 33 samples of IOLs consisting of 16 PIOLs, 12 IOLs with a central nervous system (CNS) lesion at diagnosis (IOCNSL), and five secondary IOLs following systemic lymphoma. All were B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Along with those reports, our study confirmed that the detection of IL‐10 could reflect the status of the disease in the vitreous. We previously reported the correlation between gain of the IL‐10 gene and intravitreal IL‐10 concentration . These findings indicated that IL‐10 was secreted to the vitreous from the infiltrating lymphoma cells.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Along with those reports, our study confirmed that the detection of IL‐10 could reflect the status of the disease in the vitreous. We previously reported the correlation between gain of the IL‐10 gene and intravitreal IL‐10 concentration . These findings indicated that IL‐10 was secreted to the vitreous from the infiltrating lymphoma cells.…”
Section: Discussionmentioning
confidence: 81%
“…We previously reported the correlation between gain of the IL-10 gene and intravitreal IL-10 concentration. (2) These findings indicated that IL-10 was secreted to the vitreous from the infiltrating lymphoma cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Loss of heterozygosity in the PTPRK coding region on chromosome 6 is associated with malignant glioma [76], central nervous system lymphomas [77], primary intraocular lymphoma [78], and pancreatic cancers [79]. The PTPRK gene is mutated in HNSCC [67], and a mutated PTPκ was identified as a melanoma antigen on CD4 + T-cells [80].…”
Section: Alteration Of R2b Rptps In Cancermentioning
confidence: 99%
“…Low levels of PTPκ transcripts are observed in breast cancer tissue [85] and in 20% of melanoma cells and tissue biopsies [86]. The consensus is that PTPκ is a tumor suppressor, as reduced PTPκ expression is correlated with shorter disease free-survival times in breast cancer [85], and loss of heterozygosity of the PTPRK region of chromosome 6 is associated with shorter patient survival with CNS lymphoma and primary ocular lymphoma [77, 78]. In at least one instance, however, PTPκ has a hypothesized oncogenic function as an inhibitor of apoptosis [87].…”
Section: Alteration Of R2b Rptps In Cancermentioning
confidence: 99%